Fluoroscopy reduction during device implantation by using three‐dimensional navigation. A single‐center experience. (20th August 2019) - Larsen, Timothy R.; Saini, Aditya; Moore, Jessica; Huizar, Jose F; Tan, Alex Y; Ellenbogen, Kenneth A.; Kaszala, Karoly
Abstract: Background and objectives: The use of nonfluoroscopic three‐dimensional electroanatomic mapping (3DM) systems reduces radiation exposure during ablation procedures. In this study, we sought to determine the value of 3DM during routine device implant procedures. Methods: Seventy nonselected patients underwent implantation of a single chamber, dual chamber, or biventricular device guided by Ensite (Abbott Laboratories) to limit fluoroscopy use and compared with 70 consecutive patients, who underwent matching procedures with standard fluoroscopy use (FL) in the period immediately preceding the use of 3DM. The venous anatomy, right atrium, and ventricle and coronary sinus were mapped with 0.035 inch J‐wire, quadripolar catheter, and/or angioplasty wire. The leads were advanced under real‐time visualization in Ensite. Results: 3DM reduced both fluoroscopy time and dose. Median fluoroscopy time for FL vs 3DM was 5.5 minutes (interquartile range [IQR]: 3.8‐8.1) vs 0.9 minutes (IQR: 0.6‐1.9) ( P  < .001) for single chamber devices, 6.3 minutes (IQR: 5.1‐7.9) vs 3.3 minutes (IQR: 1.9‐4) ( P  < .001) for dual‐chamber devices, and 28.6 minutes (IQR: 19.6‐36.2) to 14.7 minutes (IQR: 10.4‐22.3) ( P  = .009) for biventricular devices, respectively. The median air kerma for FL vs 3DM was 15.4 mGy (IQR: 8.1‐30.2) vs 4 mGy (IQR: 1.8‐8) ( P  < .001) for single chamber devices, 16 mGy (IQR: 12‐18.5) to 9.4 mGy (IQR: 7.5‐11.3) ( P  = .001) for dual‐chamber devices, and 324 mGy (IQR: 143‐668.7) to 115 mGy (IQR:77‐204) ( P  = .014) for biventricular devices, respectively. There were no procedural complications. At 3‐month follow‐up, there was no difference in voltage threshold measurements between the groups. Conclusion: The use of 3DM leads to significantly reduced fluoroscopy time and fluoroscopy dose during routine device implantation.